(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
This study investigated the determinants of access to credit among cocoa farmers in Osun state, Nigeria. Specifically, the study described the socio-economic characteristics of cocoa farmers in the study area, examined the factors affecting access to credit by cocoa farmers in the study area; and identified the constraints faced by cocoa farmers in credit acquisition. The study was conducted in Osun state, south-western Nigeria. A multi-stage sampling procedure was used for selecting respondents for this study. A total number of 180 farmers were selected for the study. Data were analyzed using Descriptive statistics and logit Regression. The results for the entire respondents showed average values of 46 years for age, 25 years for year of experience, 8 persons for household size, and about 88% of the respondents have formal education. Farm size (p<0.05), income (p<0.05) and years of schooling (p<0.05) show significant and positive effects on access to credit. On the other hand, gender (p<0.05), distance to credit source (p<0.1) and interest rate (p<0.01) are significant but have negative effects on access to credit by cocoa farmers in the study area. Majority (85.6%) of the cocoa farmers acknowledged lack of collateral security as a constraint in credit acquisition, while about 71.1 % acknowledged that high interest rate was a factor hindering credit acquisition. Other factors are acknowledged in the following order: Bureaucratic procedures 60.6%, lack of information about available credit sources 45%, mode of repayment 40%, no credit association 31.1% and non- membership of farmers’-based organization had 23.3%. Following the findings of the study, government, non-governmental agencies and financial institutions should provide cocoa farmers with adequate access to credit facilities and soft loans with low interest and without collateral security. In addition, cocoa farmers should be educated on the acquisition of credit. Int. J. Agril. Res. Innov. Tech. 9(2): 57-61, December 2019